Attitudes of Saudi medical students toward the disclosure of information on cancer in eastern Saudi Arabia - Ali M Al-Amri (Wolters Kluwer Medknow Publications, 2011)
Objective: To assess the attitude of future physicians regarding the disclosure of diagnosis, prognosis, benefits, and adverse effects of therapeutic intervention if they happen to have cancer. It also examined the differences if any between regions or gender. Materials and Methods: A total of 332 medical students from University of Dammam, in the Eastern Province of the Kingdom of Saudi Arabia were surveyed using a self-administered questionnaire. The questionnaire consisted of nine questions on the attitudes to disclosure of information on cancer. This self-administered questionnaire was completed by the students in the presence of an investigator. Results: The vast majority of Saudi medical students stated that they would like to know about diagnosis of cancer (92.8%) and only 7.2% wanted information withheld from them. Further, 67% of the males and 74.1% of the females wanted family members to know (P = 0.01), but one-third (33%) did not want their family to know. Only 24.1% of the male and 21.1% of female students wanted their friends to know. In addition, -97% of the males and 98.8% of the females wanted to know the diagnosis, and 97% and 95.8% of females and males, respectively, would like to know the side effects of the therapy. Almost 95% of male and 93.4% of female students wanted to know the prognosis. Also, 98% of medical students from the Eastern Region would want the diagnosis of cancer to be disclosed compared to 73.6% of those from other regions (P = 0.01). There is no difference between the genders in attitudes toward the disclosure of the diagnosis, 94.6% and 92.2% (P = 0.38). Conclusions: There was a consensus among Saudi medical students on the knowledge of the benefits of treatment, adverse effects of therapy, and prognosis. Female students significantly more than males would like their families to be informed. Significantly more medical students from the Eastern Region than those from other regions would like the diagnosis of cancer to be disclosed.